Sexuality STD/AIDS and adolescent: i don't want to talk, i'm ashamed - Vieira, Neiva F.C.; Paiva, Tereza C.H.; Sherlock, Maria do Socorro (Brazilian Journal of Sexually Transmitted Diseases, 2001)
The fast moves HIV/Aids epidemic to women has worried the health authorities since 1996. Thus, there is a need to know adolescent girl’s perceptions related to their sexuality in order to promote better health education activities in building their confidence, and self-esteem and gaining control of their sex behaviour. This study describes girl’s perceptions and experience in the development of the sexuality before the aids epidemic. Data was collected in a government school in Fortaleza between August and November of 1999. Interviews were conducted to girls at the age between 13 and 19 years old. Also dynamic group discussion provided evidence with regards to adolescents, DST and women before the HIV/Aids. The amount of 11 teenagers took part on this research which corresponds to 28,2% of pupils. The findings were described by the girl’s commonly words of their perceptions related to theme. They shawed doubts about contraceptives methods, fear and embarrassment to talk about sex and also had great expectation about their sex behaviour in future. In conclusion the adolescent girls even though receiving information about preventive means they tend not to incorporate into practice. This attitude reinforces the idea that the infection of HIV/Aids “will never happen to me”.